Electrical and magneto-transport properties of La 0.8Sr 0.2MnO 3 - Shilan S.T.; Ewe L.S.; Abd-Shukor R. (2023)
The effects of sintering temperature on the electrical and magneto-transport properties of La 0.8Sr 0.2 MnO 3 compounds prepared by employing a chemical co-precipitation route sintered at 1120C, 1220C and 1320C are reported. The X-ray powder diffraction patterns for all samples can be indexed to the rhombohedra structure with R3C space group. The insulator-metal transition temperature remained nearly constant (291 K) for all samples. The magneto resistance (MR) values were found to decrease noticeably as the sintering temperature was increased from 1120C to 1320C. Above 0.3 T, the magneto resistance was influenced by T o values, which indicates the bending of Mn-O-Mn bond. The resistivity data were fitted with several equations in the metallic (ferromagnetic) region. In the insulating (paramagnetic) region, the variable range hopping and small polaron hopping models were used to compute the density of states at the Fermi level, N(E F), and activation energy (E a) of the electrons. The resistivities can be fitted well with ?-T 2 and ?-T 2.5 curves. The variable range hopping model and small polaron hopping model fitted very well at high temperature regions, indicating that small polaron hopping might be responsible for the conduction. La 0.8 Sr 0.2MnO 3 sintered at 1220C demonstrated the highest MR of 6.5% in 1 T magnetic field. 2011 World Scientific Publishing Company.